A bilayer conducting polymer structure for planar perovskite solar cells with over 1,400 hours operational stability at elevated temperatures - Zhao, Yicheng; Heumueller, Thomas; Zhang, Jiyun; Luo, Junsheng; Kasian, Olga; Langner, Stefan; Kupfer, Christian; Liu, Bowen; Zhong, Yu; Elia, Jack; Osvet, Andres; Wu, Jianchang; et al. (Nature Energy, 2021)
The long-term stability of perovskite solar cells remains a challenge. Both the perovskite layer and the device architecture need to endure long-term operation. Here we first use a self-constructed high-throughput screening platform to find perovskite compositions stable under heat and light. Then, we use the most stable perovskite composition to investigate the stability of contact layers in solar cells. We report on the thermal degradation mechanism of transition metal oxide contact (for example, Ta-WOx/NiOx) and propose a bilayer structure consisting of acid-doped polymer stacked on dopant-free polymer as an alternative. The dopant-free polymer provides an acid barrier between the perovskite and the acid-doped polymer. The bilayer structure exhibits stable ohmic contact at elevated temperatures and buffers iodine vapours. The unencapsulated device based on the bilayer contact (with a MgF2 capping layer) retains 99% of its peak efficiency after 1,450 h of continuous operation at 65 degrees C in a N-2 atmosphere under metal-halide lamps. The device also shows negligible hysteresis during the entire ageing period.
CRIS-Team WoS Importer:2021-12-24